Factors Contributing to Online or In-store Shopping among Academics from a Private Higher Education Institution in South Africa - Moodley, Marlini; Naidoo, Sershan (International Review of Management and Marketing, 2023)
The aim of the study was to determine the factors contributing to online or in-store shopping behaviour among academics from a private higher education institution in South Africa. In addition, the study examined types of products or services consumers are likely to purchase in-store and online and particular aspects relating to store atmosphere, as well as the challenges that were experienced using both modes of shopping. The study was conducted at a private higher education institution. A cross-sectional quantitative study was conducted among all the academics in the organisation. The study show that the majority of respondents belonged to generation X and Y and that they are more inclined to purchase from both in-store and online stores rather than a singular mode of shopping. However, there is an element of fear, anxiety and uncertainty that customers face when purchasing online. This is motivated by the Stimulus-Organism-Response (SOR) model. Factors that influence the overall purchasing decision for both online and in-store shopping include accessibility, convenience, delivery service, store aesthetics (atmosphere and ambience) and the availability of an assistant. Recommendations for retail marketing managers include the fact that they should consider a hybrid model of both in-store and online shopping. Moreover, invest in enhancing the store image of both physical stores as well as virtual online stores as the subtle atmospheric cues trigger impulse purchasing.